DISKURSUS PENDIDIKAN ANAK USIA DINI (Telaah Konsep Pemikiran Pendidikan Jalaluddin Rahmat) - Edy Mustofa; Nabil Nabil (Al Hanin, 2022)
AbstrackIslam as a teaching that is universal and applies throughout the ages not only regulates the affairs of the hereafter, but also the affairs of the world. Similarly, Islam regulates the sciences related to God and the sciences related to the worldly. Islam regulates both in an integrated manner. In the Qur'an and as-Sunnah there is actually no term religious science and general science, there is only knowledge itself and all of it comes from Allah SWT. We should support the effort to "educate the life of the nation" as the goal of Indonesian education. Each concept is also offered by several people/characters who of course have different heads of different thoughts. Indonesia has many figures who care about the importance of education. Besides KH. Ahmad Dahlan, KH. Hasyim Asy'ari, and Ki Hajar Dewantara as education leaders in Indonesia in the past, there are also modern education leaders, one of whom is Jalaluddin Rakhmat. Not infrequently, his thoughts on education are approved by various groups. One that is often discussed is about the concept of early childhood education. Jalaluddin Rakhmat, as a current Indonesian education leader, is also interested in offering his concept. Therefore, let us give a little attention to how important the concept of education offered by Jalaluddin Rakhmat. Â Keyword: Early Childhood Education, Jalaluddin Rahmat and Da'wah.